Application of CAD in Landscape Grid Space Design and Drawing. (25th April 2022) - Qiao, Shuang; Liu, Yanbin; Lee, SuYoung
Abstract : CAD technology has brought great convenience and effect to the design. This paper proposes to update the comparative analysis of the basic classical landscape grid space structure by constructing a landscape grid space design. According to the actual situation of domestic landscape grid space design and drawing, this paper highlights the role of CAD technology in landscape grid space design and drawing and provides an important basis for the subsequent application of CAD software in landscape grid space design.